2020
DOI: 10.1111/acem.14065
|View full text |Cite
|
Sign up to set email alerts
|

Academic Emergency Medicine Physicians' Anxiety Levels, Stressors, and Potential Stress Mitigation Measures During the Acceleration Phase of the COVID‐19 Pandemic

Abstract: Objective The objective was to assess anxiety and burnout levels, home life changes, and measures to relieve stress of U.S. academic emergency medicine (EM) physicians during the COVID‐19 pandemic acceleration phase. Methods We sent a cross‐sectional e‐mail survey to all EM physicians at seven academic emergency departments. The survey incorporated items from validated stress scales and assessed perceptions and key elements in the following domains: numbers of suspected COVID‐19 patients, availability of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
158
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 14 publications
15
158
0
4
Order By: Relevance
“…The high level of concern about personal safety and the safety of family and dependents found in our study is consistent with the ndings from prior pandemics and at other geographical locations affected by COVID-19. [41][42][43][44][45] Our study adds the early longitudinal perspective that safety concerns among our EM providers steadily improved. This reassuring nding and may be due, in part, to the fact that speci c wellness needs were addressed early and resources made available quickly via departmental, institutional, and community initiatives.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The high level of concern about personal safety and the safety of family and dependents found in our study is consistent with the ndings from prior pandemics and at other geographical locations affected by COVID-19. [41][42][43][44][45] Our study adds the early longitudinal perspective that safety concerns among our EM providers steadily improved. This reassuring nding and may be due, in part, to the fact that speci c wellness needs were addressed early and resources made available quickly via departmental, institutional, and community initiatives.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with other studies, a majority of EM providers in our study reported feelings of psychological distress including anxiety, stress, and fear due to COVID-19. 3 4 , 43 46 In addition, about one third to one half reported increased strain on their relationships (with partner, children, and co-workers). Factors at the individual and systems levels may contribute to these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of respondents changed their behavior with their loved ones, including decreasing levels of affection due to anxiety about transmission of the disease to loved ones. Some factors alleviated feelings of distress: access to personal protective equipment (PPE), the possibility for rapid COVID-19 testing, channels of clear communication regarding pandemic planning strategy, and the reassurance that the providers could leave if needed to care for themselves and family members [23].…”
Section: Covid-19 and Provider Wellnessmentioning
confidence: 99%